Analisis Kebijakan Penutupan Sekolah Dasar di Kabupaten Sragen dengan Teknik Delphi - Dedy Yusuf Aditya; Ai Solihah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
The closure and merger of state elementary schools (SDN) in the Sragen Regency area have become a very concerning issue, with currently 70 state elementary schools being threatened with closure due to various problems, especially a lack of enrollment. This problem is caused by several factors, including the most dominant factor which is 1) low interest of parents in enrolling their children in state elementary schools and opting for private schools instead. 2) poor school management. 3) inadequate school facilities. 4) many families moving to the city. 5) a decrease in the number of primary school-aged children. The Strategic Decision Making technique used in this research is the Delphi Technique, with 5 panelists as experts. The result of this research is that the policy of closing state elementary schools in the Sragen regency area and merging them with other elementary schools is already appropriate, but other policy decisions need to be made regarding the many schools that are still at risk of closure to enable them to survive and develop.